Epidemiological profile of patients with preterm premature rupture of membranes at a tertiary hospital in São Paulo, Brazil - Marco Aurélio Knippel Galletta; Roberto Eduardo Bittar; Isabela Agra; Eliane Cerqueira Leite Guerra; Rossana Pulcineli Vieira Francisco; Marcelo Zugaib (Clinics)
OBJECTIVE: To perform a descriptive analysis of preterm premature rupture of membranes (PPROM) cases attended in a tertiary hospital. METHOD: Retrospective analysis of medical records and laboratory tests of patients admitted to a Brazilian tertiary hospital between 2006 and 2011, with a confirmed diagnosis of PPROM and gestational age (GA) at delivery <37 weeks. RESULTS: A total of 299 pregnant women were included in the study. Nine patients evolved to abortion, and 290 pregnant women remained for the final analysis. There was initial diagnostic doubt in 17.6% of the cases. The oligohydramnios rate [amniotic fluid index (AFI) <5] was 27.9% on admission. Chorioamnionitis was initially diagnosed in 10.8% of the patients and was retrospectively confirmed in 22.9% of the samples. The latency period had a mean of 9.1 days. The main reasons for interruption were premature labor (55.2%), GA ≥36 weeks (27.2%), and fetal distress (6.9%). The delivery method was cesarean section in 55% of cases. The mean birth weight was 2,124 grams, and 67% of the neonates had a low birth weight (<2500 g). The GA at delivery averaged 33.5 weeks. The stillbirth rate was 5.3%, and the early neonatal mortality rate was 5.6%. There were complications at delivery in 18% of mothers. CONCLUSION: In one of the few Brazilian reports on the epidemiological profile of PPROM, with GA until 37 weeks and intercurrences generally excluded from assessments (such as twinning and fetal malformations), there is a favorable evolution, with an acceptable rate of complications.